Navigating Barriers: Healthcare Anchor Institutions and Population Health Advancement - Wagner, Daniel; Lagu, Tara; Haywood, Carol; Schafer, Carolyn; Ackermann, Ronald (International Journal of Medical Students, 2024)
Background: Many United States hospitals explicitly pursue “anchor missions” by committing to intentionally apply place-based economic power and human capital in partnership with the community. Little is known about how hospital-community partnerships are implemented or whether they impact social determinants of health (SDOH) and population health. We qualitatively analyzed healthcare institutions from a national network to understand barriers and facilitators while implementing hospital-community partnerships that aim to improve population health. Methods: We used qualitative analysis of responses to open-ended items on a cross-sectional survey to explore how hospitals with anchor missions address SDOH. We administered the survey to healthcare systems participating in the Healthcare Anchor Network (HAN), a national network of hospitals with explicit goals to address SDOH and improve population health. Results: Responses were from 16 organizations. Two themes emerged: 1) healthcare systems faced many demands (i.e., COVID-19, financial stability), which competed with prioritization of the anchor mission, and 2) senior leadership engagement was critical for impact of the anchor mission and efforts to address SDOH and population health. Strategies to engage leadership included peer networking and providing repetitive education on community health inequities to hospital leaders. Conclusions: Although health systems show enthusiasm for population health, competing priorities often constrain anchor mission efforts to improve SDOH and population health outcomes. With external encouragement, such as changes to federal or state quality metrics reporting, payment incentives to address community health, or other policy changes, health systems will engage more with communities and be able to address SDOH.